Whale Optimization Algorithm Based Technique for Distributed Generation Installation in Distribution System - Mohd Nurulhady Morshidi; Ismail Musirin; Siti Rafidah Abdul Rahim; Mohd Rafi Adzman; Mohamad Hatta Hussain (Institute of Advanced Engineering and Science, 2018)
This paper presents Whale Optimization Algorithm (WOA) Based Technique for Distributed Generation Installation in Transmission System. In this study, WOA optimization engine is developed for the installation of Distributed Generation (DG). Prior to the optimization process, a pre-developed voltage stability index termed Fast Voltage Stability Index (FVSI) was used as an indicator to identify the location for the DG to be installed in the system. Meanwhile, for sizing the DG WOA is employed to identify the optimal sizing. By installing DG in the transmission system, voltage stability and voltage profile can be improved, while power losses can be minimized. The proposed algorithm was tested on 30-bus radial distribution network. Results obtained from the EP were compared with firefly algorithm (FA); indicating better results. This highlights the strength of WOA over FA in terms of minimizing total losses.